LRBA in the endomembrane system (2018)
ABSTRACT: Bi-allelic mutations in LRBA (from Lipopolysaccharide-responsive and beige-like anchor protein) result in a primary immunodeficiency with clinical features ranging from hypogammaglobulinemia and lymphoproliferative syndrome to inflammatory bowel disease and heterogeneous autoimmune manifestations. LRBA deficiency has been shown to affect vesicular trafficking, autophagy and apoptosis, which may lead to alterations of several molecules and processes that play key roles for immunity. In this review, we will discuss the relationship of LRBA with the endovesicular system in the context of receptor trafficking, autophagy and apoptosis. Since these mechanisms of homeostasis are inherent to all living cells and not only limited to the immune system and also, because they are involved in physiological as well as pathological processes such as embryogenesis or tumoral transformation, we envisage advancing in the identification of potential pharmacological agents to manipulate these processes.